Tradition and Modernization in the Transformation of Ma'had Aly in Indonesia - Doni Setyawan; Ananda Qomaruzzaman; Robiul Ngalim; Ifada Retno Ekaningrum (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study analyzes the role of Ma'had Aly as a guardian of Islamic traditions and scholarly authority, identifies contemporary educational challenges, and formulates strategies for institutional strengthening through a qualitative approach utilizing a library research method. Data were obtained from regulations governing pesantren and religious higher education, as well as Scopus-indexed and Sinta-accredited journal articles published in the past decade. Data analysis involved content and thematic analysis, including data reduction, coding, categorization, cross-source comparison, and conclusion drawing. Findings indicate that Ma'had Aly maintains scholarly authority through mastery of classical Islamic texts (kitab kuning), chains of transmission (sanad), specialized fields (takhassus), the kiai-student relationship, deliberation (musyawarah), legal discourse (bahtsul masail), and the development of the istinbat method. These traditions are dynamic, evolving through methodological, contextual, critical, and maqasidi approaches. Key challenges include higher education standardization, curriculum relevance, limited research culture, human resource quality, digital transformation, and quality assurance. Institutional strengthening should prioritize an integrative curriculum, faculty competency enhancement, research development, digitization of scholarly sources, network expansion, and quality assurance that integrates formal indicators with the epistemic characteristics of pesantren. The study underscores the importance of selective modernization that reinforces, rather than displaces, the traditions and scholarly authority of Ma'had Aly.